2017
DOI: 10.1111/micc.12399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of direct cold atmospheric plasma (diCAP) on microcirculation of intact skin in a controlled mechanical environment

Abstract: ObjectiveThe microcirculatory response of intact human skin to exposure with diCAP for different durations with a focus on the effect of implied mechanical pressure during plasma treatment was investigated.MethodsLocal relative hemoglobin, blood flow velocity, tissue oxygen saturation, and blood flow were monitored noninvasively for up to 1 hour in 1‐2 mm depth by optical techniques, as well as temperature, pH values, and moisture before and after skin stimulation. The experimental protocol (N = 10) was set up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
2
18
1
Order By: Relevance
“…Consistently elevated parameters even at the end of measuring period indicated that effects may possibly persist for a longer period of time. Borchardt et al found that microcirculation parameters stayed elevated for up to one hour after application of CAP in healthy skin 39 . How long those effects stay elevated in chronic wounds may be subject to upcoming studies.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently elevated parameters even at the end of measuring period indicated that effects may possibly persist for a longer period of time. Borchardt et al found that microcirculation parameters stayed elevated for up to one hour after application of CAP in healthy skin 39 . How long those effects stay elevated in chronic wounds may be subject to upcoming studies.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the optical techniques for measuring of oxygenation parameters such as laser Doppler fluxometry with transcutaneous oxygen-monitoring [56,57], as well as tissue oximeters [58], penetrate up to 1-2 mm from wound surface, HSI has the archives deeper layers up to 6 mm similarly to NIR spectroscopy [10]. HSI technology was translated into medicine in several medical applications in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported in other studies. Plasma increased the skin temperature with 2°C (Borchardt et al 2017 ; Fluhr et al 2012 ) or resulted in a sensation of heat score of 0–5 (Daeschlein et al 2012a ; Daeschlein et al 2012b ). Application of 42°C for 30 seconds could be well tolerated by volunteers (Oliveira et al 2014 ) and stimulated blood flow, while fast heating resulted in a higher endothelial activity (Del Pozzi et al 2016 ; Hodges et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The erythema index is proportional to the haemoglobin content of the upper layers of the dermis and thus might be considered an indirect measure for microcirculation, although in scars a correlation between microcirculation as measured by laser Doppler imaging and erythema was not found (Jaspers et al 2017b ). Plasma can stimulate microcirculation of healthy skin beyond the treatment time (Borchardt et al 2017 ; Fluhr et al 2012 ; Heuer et al 2015 ; Kisch et al 2016a ; Kisch et al 2016b ), which can improve the healing potential especially of chronic wounds. The enhanced microcirculation is probably mediated by plasma-produced nitric oxide (NO) (Heuer et al 2015 ), which easily penetrates the skin (Ganzarolli de Oliveira 2016 ; Vercelino et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%